Analysis of Vehicle Bogie Effects on Track Structure – Non-Stationary Analysis of Dynamic Response - Moravcik, Milan (Communications - Scientific letters of the University of Zilina, 2011)
The present paper is concentrated on the analysis of in situ vibration measurements during operating conditions in the track structure for loading by current passenger trains at the new built up railway corridor in the section Bratislava – Trnava. Tests were carried out to determine the dynamic track behaviour and relative dynamic effects between the track components – the rails, the sleepers, and the ballast bed during the passage of characteristic passenger trains moving at the operating speeds 70 ÷ 130 km/h. Experimentally obtained signals of the dynamic response of track components – measured as vertical accelerations and displacements of the rails, sleepers, and ballast bed are analysed in detail as the nonstationary random signals corresponding passages of characteristic vehicle bogies (locomotives, coaches). Vertical dynamic response of these components were measured at two different locations of this section and the vertical dynamic behaviour of track components were investigated in the time domain and analysed in the frequency domain up to 500 Hz.